Political ideologies behind the literary mask (2008)
To begin with, the purpose is to bring forth latent political ideologies ingrained in the discursive weavings of two Colombian novels from the XIX century Regeneration Period: De Sobremesa by Jose Asuncion Silva and El Moro by Jose Manuel Marroquín. In or